Pengaruh Pemasaran Berbasis Pengalaman, Efikasi Diri, dan Kepercayaan terhadap Niat Beli Kembali Layanan Bus Premium - Firman Fauzi; Armelia Levana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
This study aims to analyze the effect of Experiential Marketing, Self Efficacy, and Trust in Repurchase Intentions in Royaltrans Premium Bus Services. The data used are primary data compiled using a questionnaire, data analysis using a positive Structural and Equation Model (SEM) using Partial Least Square (smartPLS 3.0). The object of this study is Royaltrans Premium Bus Service customers in the Bekasi region with four customer routes West Bekasi - Blok M, West Bekasi - Kuningan, East Bekasi - Kalideres, East Bekasi - Tebet Jatibening - Kuningan using Royaltrans Premium Bus Service. The sample used amounted to 160 respondents using Royaltrans Premium Bus Service through a purposive sampling technique. The results of the study indicate a positive and significant effect between Experiential Marketing on Repurchase Intention, Self Efficacy on Repurchase Intention, and Trust on Repurchase Intention. From the results of this study indicate the independent variable (Experiential Marketing), (Self Efficacy) and (Trust) to the dependent variable (Repurchase Intention) gives an R-square value of 0.788 which can be interpreted as the construct marketing variable Experiential Marketing, Self Efficacy and Trust of 78, 8% while 21.2% are discussed by other variables beyond those to be submitted.